PKM KONSEP PENANAMAN POHON UNTUK EKOWISATA DI DESA PANYAWUNGAN JAYA CIOMAS - Saleh, Muhammad; Yuda, Yuda; Nursafira, Nursafira; sahrullah, Ade; Pradanti, Ainia; Ilman Perdana, Bahrul (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Panyawungan Jaya Village is one of the Vocational Villages in Ciomas District. The problems faced by Panyawungan Jaya Village are, among others, the reduction of water catchment areas due to the conversion of land into settlements. This happens because the tourism sector is starting to develop and encourage high physical development such as homestays, housing, and supporting infrastructure.  Agricultural activities also tend to change the hue of nature. Many trees lying in the fields had to be cut down so as not to block the sun's rays. As a result, rainwater cannot be absorbed into the ground but flows to the surface. In addition, Panyawungan Jaya village is also vulnerable to landslides. This is because the location of the village is in the highlands and there are many critical lands that are scattered. In addition, these critical lands are not covered with plant vegetation so they are prone to landslides in the rainy season. In fact, many critical lands are located very close to residential areas and are actually used as agricultural land. This condition is certainly dangerous for the safety of local residents. Moreover, Panyawungan Jaya village is one of the tourist villages, so the disaster mitigation aspect must always be prioritized. Many vacant lands are also unutilized. In fact, if used, in addition to increasing the coverage of green areas, it is also beneficial for the welfare of the community through the products. Therefore, the reforestation movement in Panyawungan Jaya village needs to be one of the urgent programs to be carried out immediately. So that later it will indirectly support the role that has existed so far as a vocational village and a tourist village. The plants planted are annual perennials, considering that fruit commodities are not so good when grown in the highlands, besides that perennials have a strong root system and the ability to produce oxygen. Some of the commodities that can be grown include cypress, red shoots, teak dutch and acacia. The selection of perennials is expected to produce wood in the next few years and supply oxygen so that it can strengthen Panyawungan Jaya village as an ecotourism area